Advances in business and management forecasting. Vol. 10 - Lawrence, Kenneth D.; Klimberg, Ronald K. (Emerald, 2014)
The objective of this research annual is to present state-of-the-art studies in the application of forecasting methodologies to such areas as sales, marketing and strategic decision making. It is the hope and direction of this research annual to become an applications and practitioner oriented publication. Topics will include sales and marketing, forecasting, new product forecasting, judgementally based forecasting, the application of surveys to forecasting, forecasting for strategic business decisions, improvements in forecasting accuracy, and sales response models.
Keywords: Business forecasting.; Industrial management -- Forecasting.; elektronické knihy; electronic books